Perjanjian Lisensi di Indonesia - Retna Gumanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2016)
The birth of a license agreement can not be separated from the fact that the invention patent holder of technology and very little comes from Indonesian society it proves that the Indonesian people's ability to produce a new invention that can be obtained patent rights have not shown great progress and development. These conditions support and open the occurrence of an agreement on a patent license that comes from abroad. The entry of the birth of various patents and license agreement is a logical consequence of the enactment of patent laws and the globalization of the economy are on the growth and development of industrialization. The license agreement in view of the civil law, the types of agreements innominant that kind of agreement or agreements which are not regulated outside the Civil Code. Although this type of agreement is not set, but the general provisions in the preparation and execution of this patent license agreement apply the general principles of the agreement in the Civil Code.